Prognostication of papillary thyroid microcarcinoma based on preoperative ultrasound - Cohen, Samuel M.; Noel, Julia E.; Baroody, Michael; Orloff, Lisa A. (Frontiers in Endocrinology, 2023)
Background Diagnosis of papillary thyroid microcarcinoma, defined as papillary thyroid carcinoma measuring 1cm or less in greatest diameter, has increased with improvements in ultrasound technology and widespread familiarity and utilization. Given the indolent course of papillary thyroid carcinoma, active surveillance is considered an acceptable alternative to surgical resection for select patients. Candidacy for active surveillance is determined by a number of patient and tumor characteristics. Specifically, the location of the tumor within the thyroid gland plays one of the key roles in decision making. Here we evaluate characteristics of the primary tumor and distance to the thyroid capsule in association with locoregional metastases to help guide risk assessment. Methods Retrospective chart review of all thyroid surgeries performed by two surgeons at one medical center from 2014-2021 to evaluate characteristics of papillary thyroid microcarcinoma on preoperative ultrasound that are associated with locoregional metastatic disease. Results Our data show a sensitivity of 65% and specificity of 95% for identifying regional metastases in papillary thyroid microcarcinoma using preoperative ultrasound. We found no correlation between regional metastasis and size of tumor, distance to thyroid capsule or trachea, tumor contour, or presence of autoimmune thyroiditis. Nodules in the superior or midpole were associated with central or lateral neck metastases, whereas nodules in the isthmus or inferior pole were only associated with central neck metastases. Conclusions Active surveillance may be a reasonable option for even those papillary thyroid microcarcinomas adjacent to the thyroid capsule.